Integration of genomic analysis and transcript expression of ABCC8 and KCNJ11 in focal form of congenital hyperinsulinism - Wieland, Ilse; Schanze, Ina; Felgendreher, Ina Marianti; Barthlen, Winfried; Vogelgesang, Silke; Mohnike, Klaus; Zenker, Martin (Frontiers in Endocrinology, 2022)
ABSTRACT Background: The focal form of CHI is caused by a paternally inherited autosomal recessive mutation in genes ABCC8 or KCNJ11 and a second somatic event specifically occurring in the affected islet of Langerhans. The approach of this study was to integrate the genetic changes occurring in pancreatic focal lesions of CHI at the genomic and transcriptional level. Results: Both genes, ABCC8 and KCNJ11, are located in proximity to the Beckwith-Wiedemann (BWS) imprinting control region on chromosome 11p15. Somatic paternal uniparental isodisomy (UPD) at chromosome 11p was identified as second genetic event in focal lesions resulting in LOH and monoallelic expression of the mutated ABCC8/KCNJ11 alleles. Of five patients with samples available for microarray analysis, the breakpoints of UPD on chromosome 11p were different. Samples of two patients were analyzed further for changes in gene expression. Profound downregulation of growth suppressing genes CDKN1 and H19 was detected in focal lesions whereas growth promoting gene ASCL2 and pancreatic transcription factors of the endocrine cell lineage were upregulated. Conclusions: Paternal UPD on the short arm of chromosome 11 appears to be the major second genetic event specifically within focal lesions of CHI but no common breakpoint for UDP can be delineated. We show for the first time upregulation of growth promoting ASCL2 (achaete-scute homolog 2) suggestive of a driving factor in postnatal focal expansion in addition to downregulation of growth suppressing genes CDKN1 and H19.